The Meaning And Function Of Rerajahan In The Religious Life Of The Balinese Hindu Community - Werdiyasa, I.B. Komang Surya (Bali Tourism Journal, 2024)
This abstract provides an overview of rerajahan, a form of sacred symbolism prominent in Bali, often referred to as the Island of the Gods. Rerajahan consists of small cloth pieces adorned with intricate images and inscriptions, such as human figures, mythical creatures, and sacred motifs, displayed on structures like homes and shrines. These symbols, embodying both artistic and spiritual dimensions, serve to invoke blessings and protection, reflecting the deep cultural and spiritual practices of the Balinese community. The term "rerajahan" originates from "rajah," indicating an inscription or image with mystical power. In Balinese Hinduism, rerajahan is classified into two types: "rerajahan pengiwa" (left-hand path) and "rerajahan penengen" (right-hand path), each with distinct spiritual roles. These symbols are not mere decorations but require specific rituals, known as "pasupati," to activate their spiritual efficacy. The process of creating and activating rerajahan integrates sacred scripts, such as Modré, with symbolic imagery to harness their magical properties. Rerajahan plays diverse roles in Balinese rituals and daily life, including protection, healing, and enhancing spiritual well-being. It features prominently in religious ceremonies like the Panca Yadnya rituals and is used in offerings and personal amulets. The complex Balinese script and careful selection of media for rerajahan highlight its cultural and religious significance. Whether depicted on cloth, metal, or other materials, rerajahan represents a profound connection to the divine, underscoring its importance in both sacred and everyday contexts within Balinese Hinduism.